2015
DOI: 10.1016/j.proeng.2015.01.474
|View full text |Cite
|
Sign up to set email alerts
|

Heat Dissipation in Turning Operations by Means of Internal Cooling

Abstract: Coolants and cooling strategies are just as important for the cutting process as the materials and tools themselves but do not get enough attention. There is an enormous potential for savings such as increase of the productivity and efficiency. The appropriate selection or combination of coolant strategy and coolants has furthermore enormous influence on various parameters of the surface quality and safety at work. Known and examined technologies such as dry machining or minimum quantity cooling lubrication ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Although, cutting fluids are beneficial in the industries, today their uses has been questioned around the world, due to environmental consciousness enhanced laws and regulations [34]. The use of cutting fluids has several adverse effects such as environmental pollution, dermatitis to operators, water pollution and soil contamination during disposal [35][36][37].…”
Section: Hardened Steel Turning Applicationmentioning
confidence: 99%
“…Although, cutting fluids are beneficial in the industries, today their uses has been questioned around the world, due to environmental consciousness enhanced laws and regulations [34]. The use of cutting fluids has several adverse effects such as environmental pollution, dermatitis to operators, water pollution and soil contamination during disposal [35][36][37].…”
Section: Hardened Steel Turning Applicationmentioning
confidence: 99%
“…Siller et al [8] performed experiments to determine the heat dissipated during the turning operations by using internal cooled cutting tools. They measured the temperature at the inlet and outlet of the cooling channels and found that the temperature of the tool tip were lower than the temperature obtained during dry machining.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the cutting oils can reduce friction generated between cutting tool and workpiece as well as high temperature production during a process by dissipating the initiated heat. To highlight, letting the cutting oils to flow over the tool and workpiece [2] can avoid destruction of workpiece material and cutting tool due to the thermal damage during the cutting process. Therefore, providing a great cooling and lubricating effects can improve manufacturing operations and thus increase productivity.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure cooling machining is among the most effective ones as it utilizes coolant jets with accurate alignment and extremely high pressure. Despite widely used in machining tough materials in aerospace industry [2], cryogenic cooling machining is characterized as an ecological machining technology since it applies liquid nitrogen or frozen carbon dioxide as the coolant. Furthermore, minimum quantity cooling lubrication (MQCL) machining is said to be more effective and productive as it can be used in universal condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation